2008
DOI: 10.1111/j.1525-1438.2007.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Silent killer of the night: a feasibility study of an outreach well-women clinic for cervical cancer screening in female sex workers in Hong Kong

Abstract: The purpose of this study was to see if an outreach model could be a feasible option for early detections of preinvasive cervical cancer in women with double identities of female sex workers (FSW) and illegal migrant workers in Hong Kong who most needed cervical screening but were often deprived of such a service. High turnover rates, acceptability, and compliance for follow-ups could potentially render such a clinical model unsuccessful. A total of 245 FSW were screened at the outreach clinic from January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…The remaining 13 studies focussed on international or intracontinental migration moving from low-income or middle-income to high-income countries. Destination countries included Australia,23 37 Spain,29 30 Portugal,31 Italy,34 35 the Netherlands,36 UK,33 Hong Kong42 43 and Turkey 28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 13 studies focussed on international or intracontinental migration moving from low-income or middle-income to high-income countries. Destination countries included Australia,23 37 Spain,29 30 Portugal,31 Italy,34 35 the Netherlands,36 UK,33 Hong Kong42 43 and Turkey 28…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of an acute STI was consistently higher among migrants compared to non-migrants. The most frequently measured risk behaviour was condom use 23 25 33 37 42 43 46 47. Other outcomes relating to sexual behaviours included: practising of anal sex with clients47 and accepting of extra money for unprotected sex 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our current study, the prevalence of abnormal Pap smears in the general population was very similar to that reported in 1999 in our previous study. 5 In another study we conducted, 4 based on a smaller sample of 235 subjects, the prevalence of cervical intraepithelial neoplasia of all grades (I-III) combined in female sex workers was 9.8%. While in the current study, the prevalence in this group was 5.67% (LSIL + HSIL).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a much smaller data set, our previous study showed that the point prevalence of Pap smear-diagnosed cervical intraepithelial neoplasia of all grades (I-III) in female sex workers in Hong Kong was 9.8%. 4 We had also reported a corresponding prevalence in our general population (estimated over a 6-month period…”
Section: Cmementioning
confidence: 99%